Extraction and characterization of gelatin from tilapia (Oreochromis niloticus) bones - Tumambing, Vernice Kristine M. (College of Home Economics, University of the Philippines Diliman, 2016)
Gelatin is a protein extracted through the partial hydrolysis of collagen. The aim of this study was to determine the optimum extraction temperature for tilapia bone gelatin using gel strength. The optimized extraction temperature for tilapia bone gelatin was found to be at 70°C. The extracted gelatin was found to be significantly different (p<0.05) from commercial gelatin based on gel strength. The optimized tilapia gelatin was then characterized through proximate analysis and physico-chemical analysis. From the analyses conducted on the extracted tilapia bone and commercial gelatin, only the protein showed no significant difference (p>0.05). The results show poor gelatin quality due to high moisture content (16.5%), low protein content (76.6%), light orange color (L= 58.7, a= -1.86 and b= 26.41), high turbidity (18.8% T), low viscosity (0.6-0.8 cP) and low melting temperature (24°C) compared to the commercial gelatin. Only the ash content (0.1%) and pH (4.4) were within the standard. It is then recommended to use another raw material for fish gelatin extraction. It is also recommended to include fat analysis in the proximate